Theoretical and Practical Aspects of Different Cluster Set Structures: A Systematic Review - Tufano, James J; Brown, Lee E; Haff, G Gregory (Journal of strength and conditioning research, 2017)
Tufano, JJ, Brown, LE, and Haff, GG. Theoretical and practical aspects of different cluster set structures: a systematic review. J Strength Cond Res 31(3): 848-867, 2017-When performing a set of successive repetitions, fatigue ensues and the quality of performance during subsequent repetitions contained in the set decreases. Oftentimes, this response may be beneficial because fatigue may stimulate the neuromuscular system to adapt, resulting in a super-compensatory response. However, there are instances in which accumulated fatigue may be detrimental to training or performance adaptations (i.e., power development). In these instances, the ability to recover and maintain repetition performance would be considered essential. By providing intermittent rest between individual repetitions or groups of repetitions within a set, an athlete is able to acutely alleviate fatigue, allowing performance to remain relatively constant throughout an exercise session. Within the scientific literature, a set that includes intermittent rest between individual repetitions or groups of repetitions within a set is defined as a cluster set. Recently, cluster sets (CS) have received more attention as researchers have begun to examine the acute and chronic responses to this relatively novel set structure. However, much of the rest period terminology within the literature lacks uniformity and many authors attempt to compare largely different protocols with the same terminology. Additionally, the present body of scientific literature has mainly focused on the effects of CS on power output, leaving the effects of CS on strength and hypertrophy relatively unexplored. Therefore, the purpose of this review was to further delineate cluster set terminology, describe the acute and chronic responses of CS, and explain the need for further investigation of the effects of CS.
Keywords: Rest; Exercise; Muscle Strength; Resistance Training; mužské pohlaví; únava; Humans; fyziologická adaptace; dospělí; odporový trénink; cvičení; Fatigue; lidé; sportovci; Adaptation, Physiological; Athletes; Adult; odpočinek; Male; svalová síla